2020
DOI: 10.1590/1678-9199-jvatitd-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

Why does the number of dangerous species of scorpions increase? The particular case of the genus Leiurus Ehrenberg (Buthidae) in Africa

Abstract: The aim of this contribution is to bring some precise information on the reasons why the number of noxious scorpion species is constantly growing. This fact is directly associated with the zoological research on the domains generally defined as systematics and taxonomy. The classification of any zoological group is in most cases a source of problem for most biologists not directly involved with this almost confidential aspect of the zoological research. Much information has been gathered and published over two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Subsequently, four new species have been witnessed from Africa in the past few years ( Lourenço and Rossi, 2016 , Lourenço et al, 2018 , Lourenço, 2019 , Kovařík and Lowe, 2020 ). Finally, two new species were described of Leiurus from Kuwait and Mauritania ( Lourenço, 2020a , Lourenço, 2020b ). With these two new species, the total number of known species of this genus is elevated to sixteen, spread across Africa and the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, four new species have been witnessed from Africa in the past few years ( Lourenço and Rossi, 2016 , Lourenço et al, 2018 , Lourenço, 2019 , Kovařík and Lowe, 2020 ). Finally, two new species were described of Leiurus from Kuwait and Mauritania ( Lourenço, 2020a , Lourenço, 2020b ). With these two new species, the total number of known species of this genus is elevated to sixteen, spread across Africa and the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…Hendrixson et al (2006) [47] reported a misidentification of A. amoreuxi from Medina in Saudi Arabia early in the 20th century. Lourenço (2020) [48] referred to misidentified samples of L. quinquestriatus that were collected from Mali and Algeria, i.e., out of the natural range of that species. Orthochirus innesi, whose geographical range is naturally in the North of Africa in close relation to oases, has been referred to in some works as a Sudanese species, despite not having been confirmed [49].…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be the case for several Old World genera comprising some of the most noxious species such as Androctonus, Leiurus and Buthus, which can be placed in a high or even very high evolutionary level within the buthoid lineage, but also that of some less noxious species belonging to the genera Buthacus, Buthiscus Birula and Cicileus. As for many Mesozoic fossil species these groups evolved again to telsons with quite long aculei [22,23]. The positive action of these powerful toxins most certainly authorized the evolution of possible more fragile aculei, which are, however, more performant to sting.…”
Section: Discussionmentioning
confidence: 99%